(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in national economic development. Tanjungsari Hamlet, located in Ngadirojo Village, Magelang Regency, has considerable MSME potential that remains underutilized, particularly in terms of business legality and digitalization. To address this issue, a community service program (KKN) was implemented to assist MSME actors in obtaining a Business Identification Number (NIB), developing business branding, and integrating business locations into Google Maps. The program was carried out using a door-to-door approach involving seven MSME participants, with activities including observation, interviews, and technical mentoring. As a result, five new NIBs were successfully registered, while two MSMEs already had prior business licenses (one of which was halal-certified). In terms of digital integration, all seven businesses were assisted in Google Maps registration, but only one MSME successfully passed verification. Branding improvements included the creation of Google Maps business profiles, training in social media utilization (WhatsApp, Facebook, TikTok), and culinary rebranding efforts to enhance customer recognition. Despite facing challenges such as limited understanding of OSS and NIB registration procedures, digital branding knowledge gaps, and administrative hurdles, these were overcome through direct technical assistance and practical digital marketing education. Evaluation results indicated positive responses and satisfaction from participants, with MSME actors expressing increased awareness, understanding, and readiness to operate legally and digitally. In conclusion, this program demonstrates that targeted mentoring can strengthen MSME legality, enhance digital visibility, and improve competitiveness. It provides a replicable model of MSME digital transformation that supports local economic empowerment in the digital economy era.